The Animal and the Artist in the Contemporary era: a Matter of Stylistic Code - Rinaldi, Maddalena (E|C, 2020)
The history of art, since its beginnings, tells us how the animal has always been the undisputed protagonist of artistic representations: from rock graffiti in caves to the most recent contemporary aesthetic forms, there are countless examples that should be counted in the attempt to reconstruct the evolution both aesthetic and conceptual, of the secular relationship between man and animal. This undertaking, as arduous as it is interesting, which the following work attempts to address through a necessary contextualization of the phenomenon within a time frame limited to the last thirty years. In this historical period, in fact, more than before, subject-object and life begin to mix so much to redefine aesthetic boundaries and art forms, questioning and rethinking concepts hitherto consolidated as exhibition, artist and work.